Mandibular orthopedic advancement in different facial patterns and distinct stages of skeletal maturation - Fernando Penteado Lopes da SILVA (Dental Press Editora, 2021)
ABSTRACT The Herbst appliance can be very effective in treatment of Class II patients with mandibular retrognathism. Because of the continuous action in a full-time basis, treatment time using it normally takes from six to ten months, and is usually followed by a second phase of full fixed appliances, in order to obtain both occlusal refinement and long term stability. Despite Herbst appliance's effectiveness in the occlusal and dentoalveolar perspectives, its facial results may differ among patients with different growth patterns, as well as in distinct stages of skeletal maturation. In the current paper, two patients with different facial patterns are presented, who were treated under the same protocol, using Herbst and full fixed appliances in different skeletal maturation stages, and both dentoalveolar and facial results are compared and discussed.